2016
DOI: 10.1242/jeb.134890
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-based plant defences, tooth wear and voles

Abstract: Plant-herbivore interactions are hypothesized to drive vole population cycles through the grazing-induced production of phytoliths in leaves. Phytoliths act as mechanical defences because they deter herbivory and lower growth rates in mammals. However, how phytoliths impair herbivore performance is still unknown. Here, we tested whether the amount of phytoliths changes tooth wear patterns. If confirmed, abrasion from phytoliths could play a role in population crashes. We applied dental microwear texture analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
(92 reference statements)
0
31
0
11
Order By: Relevance
“…, ; Calandra et al . ). A study of Japanese sika deer ( Cervus nippon ) across (mainly closed) habitats similarly found that both the degree of mesowear (measuring the macroscopic effects of abrasion during the tooth's lifespan) and molar wear rates were correlated with the dietary percentage of grass as well as the phytolith content of ingested grasses (Ozaki Kubo & Yamada ).…”
Section: Evolutionary Process: Mechanisms Of Herbivore Deterrencementioning
confidence: 97%
“…, ; Calandra et al . ). A study of Japanese sika deer ( Cervus nippon ) across (mainly closed) habitats similarly found that both the degree of mesowear (measuring the macroscopic effects of abrasion during the tooth's lifespan) and molar wear rates were correlated with the dietary percentage of grass as well as the phytolith content of ingested grasses (Ozaki Kubo & Yamada ).…”
Section: Evolutionary Process: Mechanisms Of Herbivore Deterrencementioning
confidence: 97%
“…Furthermore, Calandra et al . () found effects of silicon on microwear patterns in the teeth of voles and have proposed this as a mechanism by which silicon may contribute to population crashes. Hummel et al .…”
Section: Impacts Of Silicon Defences On Herbivores Vary With Herbivormentioning
confidence: 98%
“…The common view has been that the main function of foliar Si accretions in solid form (e.g., phytoliths) is to protect plant tissues from herbivory (Cooke et al, ; Epstein, ; Hartley & DeGabriel, ; Hartley, Fitt, McLarnon, & Wade, ), especially from being eaten by (mostly mammalian) vertebrates (Massey & Hartley, ; Massey, Massey, Ennos, & Hartley, ; Strömberg et al, ; Teaford, Lucas, Ungar, & Glander, ; Wieczorek, Zub, Szafrańska, Książek, & Konarzewski, ) or invertebrates (Garbuzov, Reidinger, & Hartley, ; Hunt, Dean, Webster, Johnson, & Ennos, ; Johnson et al, ; Massey & Hartley, ; Reynolds, Keeping, & Meyer, ; Ryalls, Hartley, & Johnson, ; Soininen, Bråthen, Jusdado, Reidinger, & Hartley, ), and to act as a potentially cheap alternative to cellulose or lignin (Cooke & Leishman, ; Raven, ; Schoelynck et al, ). Silicon is even thought to have played a central role in the co‐evolution of grasses and their mammalian grazers, which had to evolve teeth that could withstand chronic erosion by foliar phytoliths, although this role is still under active debate (Calandra, Zub, Szafrańska, Zalewski, & Merceron, ; Hartley & DeGabriel, ; Strömberg et al, ). However, horsetails (Equisetopsida), which generally have a very high tissue Si concentration ([Si]; in milligrams per gram dry weight; Hodson, White, Mead, & Broadley, ), are known to have been abundant as early as the Carboniferous (Trembath‐Reichert, Wilson, McGlynn, & Fischer, ), when herbivorous vertebrates had hardly evolved or not yet evolved (Sues, ).…”
Section: Introductionmentioning
confidence: 99%